ATMOSFER CAFE PENGARUHNYA TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN CAFE PASIR PUTIH DI KOTA AMBON - Etvin R. Tamher; Walter Tabelessy; Grace Tahapary (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
The rise of competition in the culinary field today, makes entrepreneurs to innovate and be creative in order to continue to increase their selling value and positioning among other competitors. One important factor that needs to be considered by culinary entrepreneurs is the atmosphere of the cafe. It is inevitable that the cafe atmosphere is one of the factors of visitors when choosing a place to gather because the cafe atmosphere is a physical characteristic that is very important in creating a comfortable atmosphere for consumers who are in the cafe and can indirectly affect the consumer picture and buying behavior. This study aims to determine customer loyalty based on the influence of the café atmosphere and customer satisfaction so that customers make transactions on an ongoing basis. The population in this study were all customers of the White Sand Cafe. From this population 100 customers were selected to be the sample in this study. Sampling is done by using purposive sampling technique. The data analysis process uses IBM SPSS ver. 23 and PLS-SEM approach with XLSTAT. As a result, the café's atmosphere has an effect on customer satisfaction and loyalty of the Pasir Putih Cafe in Ambon City. Keywords: Cafe Atmosphere, Satisfaction, Customer Loyalty